1993
DOI: 10.1111/j.1540-8159.1993.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Fluoxetine Hydrochloride for Prevention of Resistant Upright Tilt Induced Syncope

Abstract: Recurrent vasovagally mediated episodes of hypotension and bradycardia are a common cause of recurrent syncope that can be identified by head-upright tilt table testing. Although the use of beta blockers, transdermal scopolamine, disopyramide, and fludrocortisone may be helpful in preventing further episodes, some patients are intolerant of or respond poorly to each of these agents. Following anecdotal observations, we investigated the utility of fluoxetine (a serotonin re-uptake antagonist) in preventing head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…In general, while the results have been satisfactory in uncontrolled trials or shortterm controlled trials [275][276][277][278][279][280][281][282][283][284][285][286][287][288] with few exceptions [132,289] , several long-term placebo-controlled prospective trials have been unable to show a benefit of the active drug over placebo [133,134,[290][291][292][293][294] with one exception [295] . In vasovagal syncope beta-blockers, owing to their negative inotropic effect, have been supposed to lessen the degree of mechanoreceptor activation associated with an abrupt fall in venous return and block the effects of elevated circulating adrenaline, but this theory has not been supported by facts.…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…In general, while the results have been satisfactory in uncontrolled trials or shortterm controlled trials [275][276][277][278][279][280][281][282][283][284][285][286][287][288] with few exceptions [132,289] , several long-term placebo-controlled prospective trials have been unable to show a benefit of the active drug over placebo [133,134,[290][291][292][293][294] with one exception [295] . In vasovagal syncope beta-blockers, owing to their negative inotropic effect, have been supposed to lessen the degree of mechanoreceptor activation associated with an abrupt fall in venous return and block the effects of elevated circulating adrenaline, but this theory has not been supported by facts.…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…Other selective serotonin reuptake inhibitors such as fluoxetine and sertraline are less well tolerated when used for vasovagal syncope. 94,96 Clinical experience has not replicated the dramatic results of the one randomized trial.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…[5][6][7] Recently, Girolamo et al 5 demonstrated the effectiveness of paroxetine hydrochloride (Paxil, SmithKline Beecham) in reducing tilt and recurrent syncope in patients with refractory NMS. The postulated mechanism of action is an increase in central serotonin levels, which results in down-regulation of serotonin receptors, and thus attenuates any short-term, sudden shifts in central serotonin levels.…”
mentioning
confidence: 99%